(untitled) (Research, Society and Development, 2021)
There are innumerable ways of healing in a natural way, just knowing the knowledge about each plant and its true function. Nature offers humans simple methods, although caution and determination are needed to achieve great results, as drug manipulated contracting addiction inserts humans into a universe that will hardly understand the true meaning of living in harmony with nature. Nature and natural anxiolytics can be the great heroes to combat anxiety, stress, and depression, the great villains in our lives. The aim of this study is to perform an integrative literature review using scientific articles and research of publications inherent to the subject, such as articles and magazines in the pharmaceutical area. We found 12 papers that were carefully analyzed by titles and abstracts, but we concluded our research with 9 articles that met the criteria that addressed the use of natural plant extracts as a treatment strategy for anxiety. Although many of these natural anxiolytics are already being studied and used for this purpose, there are still relevant aspects that need further study. Thus, it is believed that this study will help in the alternative treatment protocols for people with anxiety, adding positively with the existing contents on the subject.